Therapeutic resources in the prevention and rehabilitation of falls in the elderly (Research, Society and Development, 2022)
Aging is permeated by several changes, among them the deficits related to balance, causing a high incidence of falls and consequently physical disability and loss of functional independence of the elderly, in which physical therapy plays a fundamental role in their rehabilitation, as well as in the prevention of diseases, aiming at the restoration of activities aimed at functionality. The general objective of the study is to describe the therapeutic resources in the prevention and rehabilitation of falls against the elderly. This is an integrative literature review, where articles were searched in academic texts from electronic libraries such as VHL, PUBMED and PEDro (Physiotherapy Evidence Database), using the following descriptors in English and Portuguese: “Primary Prevention”, “Accidental Falls”, “Aged”, “Teaching” and “Physical Therapy”, “Primary Prevention”, “Accidents from falls”, “Elderly”, Teaching and “Physiotherapy” between 2016 and 2020. 11 articles were selected for the elaboration of this review, where according to the analyzed studies, the most used physiotherapy programs were warm-up, stretching, strengthening, static and dynamic balance training, pilates, virtual reality, among others more daring that also achieved satisfactory results. There is strong scientific evidence on the intervention of various techniques in fall prevention programs. Therefore, the use of strength training, resistance, aerobic training is effective, as well as the intervention of pilates, flexibility or Proprioceptive Neuromuscular Facilitation so that they can achieve a considerable level of independence and contribute to the reduction of falls in the elderly population at high risk.